Satchel Paige : striking out Jim Crow - Sturm, James, 1965-; Tommaso, Rich (Disney/Jump at the Sun, 2019)
A graphic novel that brings the life and accomplishments of Satchel Paige to light through the experiences of fictional baseball player Emmet Wilson.